Mapping Agricultural Enterprises Index: Growth Engine to Rural Economy (with Special Reference to Uttar Pradesh) - Deepak Srivastava, Vikas (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
In any economy agrarian sector occupies one of decisive ingredients for scripting the saga of economic growth and consequently social and political cohesion. In case of developing economy, its role has been vocal enough right from Newtonian age of society down to industrial and post-industrial time horizons. Agricultural sector is complex world itself, comprising of sets of multitude agricultural practices like farming, dairy, Seri culture, flower cultivation and other allied practices dependent either directly or indirectly on all these practices. Agri enterprises are those enterprises based and run by inputs procured by agricultural sector. Since ages, Traditional and cottage enterprise have been looked upon for major source of rural employment and fuel for economic and social prosperity too. Even after 74th years of independence, and so many economic twist and turns followed by recent year century worst medical crisis, rural and agricultural enterprises have meticulously stood by vast section of demographic dividends fell into vulnerability trap posed by medical crisis. In this paper, an attempt was made to gauge the track of agricultural enterprises with help of index computed by taking the agri enterprises statistics published in Uttar Pradesh District statistical diary for year 2019-20. Data regarding to operating agricultural and non agri cultural enterprise in economic census conducted regularly in each district. General index calculation approach was adopted on given indicator with minimum and maximum value within universe of districts in question.